CAMKV Is a Candidate Immunotherapeutic Target in MYCN Amplified Neuroblastoma - Sussman, Robyn T.; Rokita, Jo Lynne; Huang, Kevin; Raman, Pichai; Rathi, Komal S.; Martinez, Daniel; Bosse, Kristopher R.; Lane, Maria; Hart, Lori S.; Bhatti, Tricia; Pawel, Bruce; Maris, John M. (Frontiers in Oncology, 2020)
We developed a computational pipeline designed to use RNA sequencing (n=136) and gene expression profiling (n=250) data from neuroblastoma tumors to identify cell surface proteins predicted to be highly expressed in MYCN amplified neuroblastomas and with little or no expression in normal human tissues. We then performed ChIP-seq in the MYCN amplified cell lines KELLY, NB-1643 and NGP to identify gene promoters that are occupied by MYCN protein to define the intersection with the differentially-expressed gene list. We initially identified 116 putative immunotherapy targets with predicted transmembrane domains, with the most significant differentially-expressed of these being the calmodulin kinase-like vesicle-associated gene (CAMKV, p=2x10-6). CAMKV encodes a protein that binds calmodulin in the presence of calcium, but lacks the kinase activity of other calmodulin kinase family members. We confirmed that CAMKV is selectively expressed in 7/7 MYCN amplified neuroblastoma cell lines and showed that the transcription of CAMKV is directly controlled by MYCN. From membrane fractionation and immunohistochemistry, we verified that CAMKV is membranous in MYCN amplified neuroblastoma cell lines and patient-derived xenografts. Finally, immunohistochemistry showed that CAMKV is not expressed on normal tissues outside of the central nervous system. Together, these data demonstrate that CAMKV is a differentially-expressed cell surface protein that is transcriptionally regulated by MYCN, making it a candidate for targeting with antibodies or antibody-drug conjugates that do not cross the blood brain barrier.